Różnice kursowe w podatkach dochodowych w działalności przedsiębiorców - Stanisławiszyn, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The issue of exchange-rate differences not only aroused alot of controversy in respect of activities undertaken by entrepreneurs taxpayers in terms of international law, but is also the subject of continuing problems and discrepancies in the practice of tax consultants, tax authorities, as well as the case law of administrative courts. In part this state of affairs is the result of the overlapping of this issue with regulations from different fields of law, i.e. balance, tax and foreign exchange trading. Another element which caused that considerations for exchange-rate differences grew in importance was and still remains the increase in the number and type of transactions in international trade, as well as national, and where settlement occurs in currencies other than the currency of Poland. The primary objective of this publication is an attempt at assessing the issues through the problems regarding exchange-rate differences, which most often appear in practice of entrepreneurs and tax authorities and tax consultants from the point of view of the provisions of the income tax acts. To a necessary extent they will be presented more as a supplementary and complementary aspects of the balance and the foreign exchange law.
Keywords: income taxes; exchange-rate differences; tax expense; tax revenue; foreign currency